Potential Utilization of Palm Oil Liquid Waste as Downstream Agroindustry Products with Proximate Test and β-Carotene Concentration - Karnadi; Adiarso; Dyah Iswantini; Sri Mulijani (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Since 2006, Indonesia has led global production and export of palm-based edible oils. Government policies focused on advancing agriculture and agro-industries, particularly in downstream product development, provide opportunities to increase the economic value of these products, including palm oil products. Efforts to enhance downstream products include maximizing all palm oil potentials, including its waste. Global CPO production based on 2024 data is 79.6 million tons per year, with Indonesia contributing 59%. The potential waste is also very large, including the final waste which still contains around 20-25% oil and 3-5% phytonutrients. Proximate analysis and β-carotene content studies are used to evaluate the potential of CPO liquid waste for poultry feed. Proximate analysis results show low nutrient levels, including protein (<0.04%), carbohydrates (1.37%), total carbohydrates (<0.02%), total energy (5.20%), and crude fiber (<0.02%), making it unsuitable as a poultry feed substitute. However, based on β-carotene data, the waste can be used as an additive in poultry feed if stored for less than 28 days. The β-carotene degradation process follows zero-order reaction at heating and storage conditions (under room and dark storage).